Profile of Calistung (Reading, Writing and Arithmetic Skills) in Early Childhood - Rahmat Hidayat; Julia Noviani (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2023)
The importance of reading, writing and arithmetic for early childhood has become a major concern for educators and parents. The calistung abilities (reading, writing and arithmetic) that children have from an early age will make it easier for them to take further education. The purpose of this study was to describe the ability to read, write, and arithmetic in early childhood. This research is a qualitative descriptive study that describes the ability to read, write and arithmetic in Keleton Senye Kindergarten, Central Aceh Regency. This research was conducted on 4 early childhood students, consisting of two boys and two girls. Data collection techniques in this study used a task sheet and semi-structured interviews. The data analysis technique used the Miles and Huberman technique; data reduction, data presentation and conclusions. The results showed that of the 4 children studied, AF subjects have not met the indicators of reading and arithmetic skills, NF subjects have not met the indicators of reading and arithmetic skills, NR subjects have not met the indicators of reading and writing skills and AM subjects have not met the indicators of reading skills. In principle, learning in early childhood is learning carried out by children through games that are given in stages that are fun and interesting for children.